ANALYSIS OF LABOR PRODUCTIVITY IN IRONING AND BEAUTIFICATION WORK USING THE WORK SAMPLING METHOD - Sopar Parulian (Journal of Information Technology, computer science and Electrical Engineering, 2026)
Labor is one of the most crucial and dynamic resources in construction projects, contributing significantly to total project costs, typically ranging from 30% to 50%. The efficiency of labor utilization directly impacts project schedule and budget targets. This study aims to analyze labor productivity in high-rise building structural works, specifically rebar binding (ironing) and formwork (begisting) installation, using the Work Sampling method. Field observations recorded proportions of effective work, essential contributory work, and ineffective work. Labor Utilization Rate (LUR) was calculated to quantify productivity. Based on a 5-day observation period totaling 1,920 sample observations, the LUR for rebar work was determined to be 65.94%, while formwork achieved 61.98%. Both values exceed the construction industry standard baseline of 50%, yet substantial room for optimization exists by mitigating ineffective work (19.79% for rebar and 22.71% for formwork). Primary causes of ineffective time include material supply delays, congested work zones, equipment shortages, and worker fatigue. Recommended improvement strategies include Just-in-Time (JIT) material delivery, optimized site layout for fabrication zones, and restructured rest break schedules.